The Last Peasants, Journeys - Macqueen, Angus (United Kingdom : October Films, 2003)
The Damian Family, once powerful under the communists, are now the poorest family in the village. Ion and Maria are desperate to leave to join his brother in Ireland or their sister-in-law in Paris. But life in Paris and Dublin is hardly a dream for the brother and sister in law. Their marriage is drifting apart as they both struggle to do much more than work and make money.
Verzio Film Festival Submission
Keywords: United Kingdom